PENGARUH PELATIHAN, KOMPENSASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. X DI JAKARTA - HENDRI PRANATA; RR. NIKEN PURBASARI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to determine any factors that may affect employee performance. Variables to be study is the influence of training, compensation, motivation, and discipline. The methods used in this research is descriptive method and causality with multiple regression method to test the hypothesis. The population of this study are all permanent employees of PT. X at Jakarta totaling 72 employees. Data for the study comes from the primary data by distributing Likert scale questionnaires to employees. The sampling method using saturated sampling method. The empirical results of this study indicate that the training, compensation and diciipline each have a positive and significant influence on employee performance, while motivation has no effect on employee performance.